Characteristics of acute myocardial infarction cases among young adults in Hospital Tengku Ampuan Afzan, Kuantan Pahang - Mohd Zhafri Mohd Razib (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Introduction: Acute myocardial infarction (AMI) is a major cause of death around the world. There are limited studies regarding the characteristics of the disease among young adults. This study aimed to study the characteristic of AMI cases among young adults presented to Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang. Method: This prospective observational study was conducted in HTAA from 31st July 2017 to 30th July 2018 involving 818 patients who were diagnosed with AMI. Inclusion criteria included Malaysian citizen aged 18 to 45 years old diagnosed with AMI and abled to give written informed consent. Results: Patients with AMI and aged less than 45 years old were 88 (10.8%). The incidence proportion of AMI cases among young adults in HTAA Kuantan, Pahang were 10.3 per 100 persons of total AMI cases over a year period (95% Confidence Interval, 8.4%-12.6%). A total of 58 patients that met the study inclusion criteria were recruited for further descriptive analysis. The median age of the patients was 40 years old (range = 24 - 45). Fifty-six (96.6%) patients were males, while 46 (79.3%) of the patients were Malays. Married patients account for 49 (84.5%) patients, and 45 (77.7%) patients had incomes less than RM 2500 that made up the majority of the young adult AMI patients. The commonest risk factors for young adults with AMI was smoking (N=45, 77.6%) followed by obesity (N=33, 56.9%), increased waist circumference (N=32, 55.2%), hyperlipidaemia (N=29, 50.0%), hypertension (N=20, 34.5%), family history of cardiovascular disease (N=20, 34.5%), diabetes mellitus (N=18, 31.0%), and alcohol consumption (N=7, 12.1%). All patients had at least one cardiovascular risk factor, while 17 (37%) patients had a single one coronary vessel involvement and left anterior descending artery was the commonest vessel involved (n=36) in the angiogram findings. Conclusion: The incidence proportion of AMI cases among young adults in Pahang was 10.3 per 100 persons of total AMI cases over a year period. It occurs exclusively in males, with smoking and obesity being the two most prevalent risk factors, unlike earlier studies which showed hypertension as the main cardiovascular risk factor. The high incidence of AMI cases in the younger age group strongly suggests that an early aggressive health intervention program needs to be conducted targeting a younger age group in the population.